2016
DOI: 10.1002/jbm.a.35940
|View full text |Cite
|
Sign up to set email alerts
|

Silk fibroin based carrier system for delivery of fibrinogen and thrombin as coagulant supplements

Abstract: The control of bleeding is one of the most important interventions after a traumatic injury. Hemostatic devices delivering blood clotting accelerating agents such as fibrinogen are increasingly used due to their efficacy and their ease of application. In the present study, we describe a method to incorporate the coagulant supplements fibrinogen and thrombin in silk protein sponges by mixing the coagulants with an aqueous silk solution, followed by molding, freeze-drying, and water annealing. In this combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Many studies have shown various materials such as fibrin-/silk- [ 15 ], polysaccharide- [ 16 ], and collagen-based adhesives [ 17 ], which can be used as soft hydrogels for hemostasis. Collagen is one of the essential extracellular matrices in gingival tissues [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown various materials such as fibrin-/silk- [ 15 ], polysaccharide- [ 16 ], and collagen-based adhesives [ 17 ], which can be used as soft hydrogels for hemostasis. Collagen is one of the essential extracellular matrices in gingival tissues [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 A few reports of silk based lyogels have been published and it has been demonstrated that the crosslinked nature of the starting protein network results in unique physicochemical properties compared to lyophilized sponges made by lyophilizing uncrosslinked silk solution. 14,[16][17][18][19] While lyophilized silk sponges have been widely explored and evaluated for applications such as soft tissue, [20][21][22] intervertebral disc, 23 and cardiovascular tissue [24][25][26] augmentation and regeneration, platelet production, 27 and drug delivery, 28,29 silk lyogels are less well characterized. In particular, the properties of silk lyogels made from di-tyrosine crosslinked silk networks have not been explored to date.…”
Section: Introductionmentioning
confidence: 99%
“…Most reported co-loaded nanoparticles have difficulty controlling the synergistic release of two or more payloads, which has a great impact on the outcomes of synergistic therapies ( Teuschl et al, 2017 ; Zhu et al, 2018 ). Herein, the PLGA nanoparticles loaded with preformed ICG@uPA realized adjustable proportion of components and synchronous release of the payloads, which meant that the NPs could serve as a suitable platform for tunable and synergistic thrombolysis via the administration of ex vivo laser.…”
Section: Resultsmentioning
confidence: 99%